Efektivitas Terapi Bekam Titik Alkahil dan Terapi Akupuntur Terhadap Tekanan Darah pada Penderita Hipertensi di Desa Karangbong Kecamatan Pajarakan Kabupaten Probolinggo - Faidah Faidah; Hamim Hamim; Rizka Rizka (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Hypertension is a widespread health problem and is often called a "silent killer" because it often has no warning signs or symptoms, and many people don't realize they have it. The purpose of this study is to determine the effectiveness of alkahil point cupping therapy and acupuncture therapy on blood pressure in hypertensive patients in Karangbong Village, Pajarakan District, Probolinggo Regency. The method in this study is Pre-Experiment, with a Two-group pre-post test design, the sample in this study is patients with hypertension totaling 36 patients who were taken using the purposive sampling instrument technique which was used were cupping devices, acupuncture tools, tension meters and observation sheets. Furthermore, it was analyzed using the Paired t-test, the Wilxocon test, the Independent t-test, and the Mann-Whitney test. The results of the study showed that before the alkahil point cupping therapy was carried out, an average value of 149/102 mmHg was obtained, and the average value before acupuncture therapy was 149/99 mmHg. After alkahil point cupping therapy , an average value of 139/92 mmHg was obtained and after acupuncture therapy was 134/90 mmHg. It is known that the average value of the pre-post sistole difference of alkahil point cupping therapy is 10.33, and the average value of the pre-post difference of acupuncture therapy is 15.00 with a pV of 0.000 which means < 0.05. Meanwhile, the average value of the pre-post diastole difference in alkahil point cupping therapy was 19.61 and acupuncture therapy was 17.39 with a pV > 0.05. It can be concluded that the average value of the difference in pre-post sistole of acupuncture therapy is more effective than alkalil point cupping therapy in reducing blood pressure in hypertensive patients Alkahil point cupping therapy and acupuncture therapy can be traditional alternative treatments that can be done routinely for the hypertension healing process by doing acupuncture therapy.